A Season of Change: How Science Librarians Can Remain Relevant with Open Access and Scholarly Communications Initiatives. - Elizabeth Brown (Issues in Science and Technology Librarianship)
The article focuses on maintaining the relevance of science librarians with new developments such as new communication initiatives and Open Access publishing. Current issues demonstrating the impact of such initiatives include the digital divide existing between the public and the research community, transformation of the physical space in the library and increasing reliance on electronic journals. Standards on interoperability in sharing library data and collections include the Encoded Archival Description (EAD) and the Dublin Core (DC).